2017
DOI: 10.1161/atvbaha.117.309683
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Ectasia Predicts Future Cardiac Events in Patients With Acute Myocardial Infarction

Abstract: The presence of CAE predicted future cardiac events in patients with acute MI. Our findings suggest that acute MI patients with CAE are a high-risk subset who might benefit from a pharmacological approach to controlling the coagulation cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
94
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 23 publications
2
94
2
9
Order By: Relevance
“…Long-term cardiovascular outcomes of patients with CAE suffering from acute coronary syndromes were always a question needing an answer. Doi et al in their study showed a significant prognostic effect of CAE in these patients with improved outcomes in cases treated with therapeutic oral anticoagulation [10].…”
Section: Introductionmentioning
confidence: 89%
“…Long-term cardiovascular outcomes of patients with CAE suffering from acute coronary syndromes were always a question needing an answer. Doi et al in their study showed a significant prognostic effect of CAE in these patients with improved outcomes in cases treated with therapeutic oral anticoagulation [10].…”
Section: Introductionmentioning
confidence: 89%
“…The clinical and prognostic significance of CAE is not clearly understood. CAE may be a cause of coronary rupture, spasm, dissection, thrombosis, myocardial ischemia and even sudden cardiac death eventually [3,4]. As a result this condition may not be accepted completely benign as it is associated with adverse coronary events [5].…”
Section: Introductionmentioning
confidence: 99%
“…У пациентов с ишемической болезнью сердца (ИБС) наличие сопутствующих АКА является независимым предиктором смертельных исходов [6,[15][16][17]. Одна из причин неблагоприятного влияния на прогноз связана с высокой вероятностью тромбирования аневризм и развитием острого коронарного синдрома (ОКС), вызванного окклюзией крупной ветви артерии либо эмболией дистального сосудистого русла фрагментами тромботических масс, вымываемых из аневризматического мешка.…”
unclassified
“…Так, известно, что АКА чаще обнаруживаются у мужчин, при этом, как и в обсуждаемом клиническом примере, поражается преимущественно ПКА [1][2][3][4][5][6]. Считаем уместным еще раз напомнить, что тромбоз АКА служит частой причиной ОКС [6,[15][16][17]. В этой связи весьма логично предположить взаимосвязь аневризмы ПКА и перенесенного инфаркта миокарда нижней локализации у представляемого больного.…”
unclassified
See 1 more Smart Citation